2022
DOI: 10.1002/jssc.202200671
|View full text |Cite
|
Sign up to set email alerts
|

A pre‐column derivatization high‐performance liquid chromatography method for simultaneous determination of short‐chain and medium‐chain fatty acids in a fecal sample

Abstract: Short‐chain and medium‐chain fatty acids have plentiful biological functions, which play a crucial role in the diagnosis and therapy of many diseases. Herein, a new method for simultaneous quantifying 17 short‐chain and medium‐chain fatty acids with high‐performance liquid chromatography coupled with an ultraviolet detector was developed and the pre‐column derivatization by indole‐3‐acetic acid hydrazide was performed to improve the separation and detection. The conditions of the derivatization reaction were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Nevertheless, it is impractical to use stable isotope labeling with high purity which was usually expensive and difficult to synthesize as the IS in the quantification of FAs. In our previous study [38], SCFAs and MCFAs in the fecal sample were derivatized using IAH and determined on HPLC, and the derivant of IAH was proved to be stable. In this study, commercially available ICH and IAH were selected as the double derivatization reagents for FAs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, it is impractical to use stable isotope labeling with high purity which was usually expensive and difficult to synthesize as the IS in the quantification of FAs. In our previous study [38], SCFAs and MCFAs in the fecal sample were derivatized using IAH and determined on HPLC, and the derivant of IAH was proved to be stable. In this study, commercially available ICH and IAH were selected as the double derivatization reagents for FAs.…”
Section: Resultsmentioning
confidence: 99%
“…To obtain satisfactory sensitivity, accuracy, and high throughput of FAs quantification, two different parameters of the derivative conditions were optimized: (1) the concentration of EDC, HOBt, and ICH, and (2) reaction temperature and time. In our previous study [38], we investigated the effect of the reaction solvent and found that the derivatization would be efficient in the methanol solvent system. Thus, all the essential derivative solvents and standard solutions were prepared with methanol.…”
Section: Resultsmentioning
confidence: 99%
“…The monosaccharide composition of IPS was analyzed using pre-column derivatization of 1-phenyl-3methyl-5-pyrazolone (PMP) integrated with high-performance liquid chromatography (HPLC) because of the optical properties of the monosaccharides [29] .…”
Section: Determination Of Monosaccharide Contentmentioning
confidence: 99%
“…Besides, a variety of methods can be used for quantitative determination, such as gas chromatography (GC) or combined mass spectrometry (MS) [22], high-performance liquid chromatography (HPLC), ion exclusion chromatography, and capillary electrophoresis [23]. Due to the weak UV absorption, it is necessary to conduct pre-column or post-column derivatization on SCFAs before HPLC [11,[24][25][26], which is more cumbersome. When analyzing SCFAs with GC, it is necessary to carry out derivation to increase signal response and improve chromatographic peak shape [27], which is also time consuming.…”
Section: Introductionmentioning
confidence: 99%